Enhancing Reading Comprehension ofGrade 12 ABM Students by Reading Vocabulary Words (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
According to Dr. Seuss, “The more that you read, the more things you will know. The more that you learn, the more places you’ll go.” To do this, people need to start with basic skills, such as reading comprehension skills and vocabulary knowledge, that will be used throughout their lives. The reader uses knowledge, skills, and strategies to determine the meaning of the word. Reading comprehension is the heart and goal of reading because the purpose of all reading is to gather relevant information from the printed page. It is an act where a person understands what he/she is reading. Thus, every reader should engage himself/herself with the texts for easy understanding. Through convenience sampling, 50 Grade 12 Accountancy, Business, and Management (ABM) students were chosen by the researchers as the respondents of this study. The survey method was also used because it is one of the easiest ways to gather relevant information. Based on the results of the study, the following are the factors that affect the reading comprehension of Grade 12 ABM students. (1) Self-confidence –It is oneofthe problems of students because they do not have enough ability to deal with many people. They find it hard to communicate with others because they do not know what are the appropriate words to say. (2) Vocabulary words –To have a deeper understanding of the texts, students must be able to comprehend the vocabulary words that are used in the piece of writing. In this case, students have difficulty regarding the correct pronunciation of some unfamiliar words. Some students face difficulty in incorporating new words as they speak. Thus, they are afraid that they may be misinterpreted by other people. Based on the results, this study determined the students’ reading performance and evaluated their strengths and weaknesses in terms of reading. Awareness about the student’s struggles with reading comprehension should be done because it is one way of enhancing the reading comprehension of the students. The quality of education should be improved, and the English language skills of the students should be developed by at least giving them tasks where the students can learn new vocabulary words.
Keywords: enhance, reading comprehension, vocabulary words